Effectiveness and Safety of Acitretin in Children with Plaque Psoriasis: A Multicenter Retrospective Analysis. Issue 5 (22nd July 2016) - Di Lernia, Vito; Bonamonte, Domenico; Lasagni, Claudia; Belloni Fortina, Anna; Cambiaghi, Stefano; Corazza, Monica; Di Nuzzo, Sergio; Gisondi, Paolo; Panzone, Michele; Guarneri, Claudio; Neri, Iria
Abstract: Background: Acitretin is licensed for and is most commonly used to treat psoriasis. Little information exists about its efficacy and safety in childhood and adolescent psoriasis. Methods: Retrospective analysis of a group of children and adolescents (<17 years of age) with moderate to severe plaque psoriasis treated with acitretin between 2010 and 2014 at Italian dermatology clinics. Patients were identified through databases or registries. Results: The study population consisted of 18 patients with a median age of 9.5 years at the start of therapy. The median maintenance dosage per day was 0.41 mg/kg. Eight patients (44.4%) achieved complete clearance or good improvement of their psoriasis, defined as improvement from baseline of 75% or more on the Psoriasis Area and Severity Index at week 16. Three had three or more courses of treatment with short disease‐free intervals. In three patients, acitretin treatment was ongoing at the time of data collection. The mean total duration of treatment in responders was 22.7 months. One patient discontinued treatment because of arthralgia. The remaining nine patients (50%) discontinued treatment because it was ineffective. Mucocutaneous adverse effects occurred in all patients, but did not affect therapy maintenance. Conclusions: In this retrospective case series, acitretin was a moderately effective, well‐tolerated treatment in children with moderate to severe plaque psoriasis. Given the small number of patients, statements about long‐term safety are not possible.